1995
DOI: 10.1002/jso.2930580305
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous carcinoma of the breast: A pathologic study of 82 cases

Abstract: A series of 82 consecutive cases of mucinous carcinomas of the female breast was investigated for their clinical, morphological, and histochemical features and for the influence of some tumor characteristics on its prognosis. Two groups, a "pure" subtype (n = 58) and a "mixed" subtype (n = 24), were considered, according to the absence or the presence of concomitant areas with typical infiltrating ductal carcinoma. Eighty patients were followed with an average of 7.4 years. The actuarial survival was 58.5% at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
1
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 15 publications
7
46
1
2
Order By: Relevance
“…This is in agreement with one study which found that when patients were divided into those with pure mucoid, mixed and minimal mucoid component, survival rates were better in those with tumours having a proportionally greater gelatinous element (Melamed et al, 1961). In contrast, another series found no impact on prognosis when patients with tumours containing 50-75% of mucoid component were compared with those having more than 75% (Andre et al, 1995). It has also been suggested that the actual proportion of mucin produced within the tumour may be of prognostic significance (Clayton 1986).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in agreement with one study which found that when patients were divided into those with pure mucoid, mixed and minimal mucoid component, survival rates were better in those with tumours having a proportionally greater gelatinous element (Melamed et al, 1961). In contrast, another series found no impact on prognosis when patients with tumours containing 50-75% of mucoid component were compared with those having more than 75% (Andre et al, 1995). It has also been suggested that the actual proportion of mucin produced within the tumour may be of prognostic significance (Clayton 1986).…”
Section: Discussionsupporting
confidence: 90%
“…Rasmussen (1985) also noted that the non-mucoid component often appeared more anaplastic. Probably, as previously suggested, there is a morphological continuum with all mixed tumours starting as pure lesions and the non-mucoid component developing at a later stage (Andre et al, 1995).…”
Section: Discussionmentioning
confidence: 60%
“…occurs in elderly female median age being older than 55-60 years. [4][5][6] This tumor shows characteristic features of mucin production by the tumor 7 and in general mucinous component is 50% or more. 8,9 In the mixed type tumor, the mucinous component is admixed with infiltrating epithelial component.…”
Section: Introductionmentioning
confidence: 98%
“…Müsinöz meme karsinomu nadir görülen bir tip olup meme karsinomlarının %1-6'sını oluşturur (1). Daha çok ileri yaş kadınlarda görülür ve prognozu iyidir (2).…”
Section: Introductionunclassified
“…Daha çok ileri yaş kadınlarda görülür ve prognozu iyidir (2). Makroskopik olarak yumuşak kıvamlı ve iyi sınırlıdır, kesit yüzeyi parlak ve jelatinöz görünümdedir (1). İyi sınırlı olmaları nedeni ile klinik, radyolojik ve makroskopik olarak benign meme lezyonlarını taklit edebilirler (3).…”
Section: Introductionunclassified